Cooperation of the Police and Family in Prevention of Cyberviolence among Children and Teenagers- a Possibility or Utopia? - Zellma, Anna (Studia Warmińskie, 2014)
In recent years various initiatives that aim at limiting and eliminating the threats connected with cyberviolence were taken. Supporting children and teenagers in responsible usage of new information technology seems to be very important. This task deserves particular parents’ attention. However, parents need help in fulfilling this task. From among different forms of support given to the family, cooperation with the police can fulfill a significant role. More and more frequently, police officers engage in diverse actions to prevent cyberviolence among children and teenagers. The analyses undertaken in this article concentrate on the following questions: is cooperation with the police and family in prevention of cyberviolence among children and teenagers possible?, isn’t it utopian?, what should be done to make such cooperation possible? A problem defined in this way requires presenting the possibilities and limitations in cooperation of the police and family in preventing cyberviolence among children and teenagers. Keeping that in mind, the notion of “cyberviolence” was described. Afterwards, the phenomenon of cyberviolence among children and teenagers was characterized. In this context the attention was paid to specific initiatives of the police and numerous legal, organizational, and social limitations.